Buildup of the Kondo effect from real-time effective action for the Anderson impurity model - Bock, Sebastian; Liluashvili, Alexander; Gasenzer, Thomas (Physical review, 2016)
The nonequilibrium time evolution of a quantum dot is studied by means of dynamic equations for time-dependent Green's functions derived from a two-particle-irreducible (2PI) effective action for the Anderson impurity model. Coupling the dot between two leads at different voltages, the dynamics of the current through the dot is investigated. We show that the 2PI approach is capable of describing the dynamical buildup of the Kondo effect, which shows up as a sharp resonance in the spectral function, with a width exponentially suppressed in the electron self-coupling on the dot. An external voltage applied to the dot is found to deteriorate the Kondo effect at the hybridization scale. The dynamic equations are evaluated within different nonperturbative resummation schemes, within the direct, particle-particle, and particle-hole channels, as well as their combination, and the results compared with those from other methods.